2016
DOI: 10.7860/jcdr/2016/21664.8587
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection by Methicillin Resistant Staphylococcus aureus– on Decline?

Abstract: being the predominant organism causing SSIs, MRSA needs the attention for its resistance to commonly used antibiotics in the hospital like penicillin, cephalosporin group of drugs. Regular monitoring of the MRSA, involved in the SSI of a particular setup is the basic requirement to trim down the incidence of the postoperative wound infections by proper antibiotic prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 21 publications
4
31
1
1
Order By: Relevance
“…In our study, the other organisms isolated included Diphtheroids (12%), E. coli (10.5%), Klebsiella (7%), Pseudomonas (7%), and Acinetobacter (2%). The main gram-negative offenders in our study were E. coli, followed by Klebsiella and Pseudomonas, this was similar to that in studies done by Bhattacharya and Anjum et al [5,19]. No growth of Streptococci was obtained.…”
Section: Microbiological Pro Lesupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the other organisms isolated included Diphtheroids (12%), E. coli (10.5%), Klebsiella (7%), Pseudomonas (7%), and Acinetobacter (2%). The main gram-negative offenders in our study were E. coli, followed by Klebsiella and Pseudomonas, this was similar to that in studies done by Bhattacharya and Anjum et al [5,19]. No growth of Streptococci was obtained.…”
Section: Microbiological Pro Lesupporting
confidence: 92%
“…Among the 19 cases with Staph aureus growth, 60% constituted MRSA. Another study by Bhattacharya et al also showed the highest culture of Staph aureus (35%) among the SSI, (of which MRSA was 26%), others being E. coli (20%), Klebsiella (18%), Pseudomonas (8%) and Acinetobacter (7.5%) [19]. In our study, the other organisms isolated included Diphtheroids (12%), E. coli (10.5%), Klebsiella (7%), Pseudomonas (7%), and Acinetobacter (2%).…”
Section: Microbiological Pro Lementioning
confidence: 85%
“…28 These infections are usually caused by exogenous or endogenous microorganisms that enter the operative wound during the course of the surgery. 29 In our study over 32 of 37 patients with history surgical site infection had positive result culture. These wound infections may have occurred at hospital and recognized to be associated with an infection before-after or during surgery, extended length of hospital stays and prolonged or permanent disability.…”
mentioning
confidence: 54%
“…In addition, prior studies in India by Surange et al [13] , Subramanian et al [14] and recent study by Kownhar et al [15] have stated the occurrence of S. aureus to be 34.2%, 30.9% and 37% respectively. Past studies revealed that 80% of healthy individuals harbor S.aureus in their skin or anterior nares and hence causes post operative wound infection when integrity of the skin is breached during surgery [16] .…”
Section: Discussionmentioning
confidence: 99%
“…The management of SSI caused by S.aureus is further complicated due to the emerging multi drug resistant strains, particularly the methicillin resistant S.aureus (MRSA), which also represents the leading cause of S.aureus associated nosocomial infections [2] . MRSA has become a hospital superbug throughout the world [16] . In the current study 39.1% of S.aureus isolates were methicillin resistant.…”
Section: Discussionmentioning
confidence: 99%